PENGARUH LEARNING ORGANIZATION DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN DELI SERDANG - Dika Hidayati; Dani Habra; Wan Dian Safina (Jurnal Inovasi Penelitian, 2022)
The title of this research is "The Influence of Learning Organization and Competence on Employee Performance at the Central Bureau of Statistics of Deli Serdang Regency". The purpose of this study was to determine and analyze the effect of learning organization and competence on employee performance at the Central Bureau of Statistics of Deli Serdang Regency. This research is an associative type of research that looks at the effect of learning organization and competence on employee performance at the Central Bureau of Statistics of Deli Serdang Regency and testing the hypothesis using Multiple Linear Regression Analysis at =5%. The population in this study were all employees of the Central Statistics Agency of Deli Serdang Regency. The sample used in this study were employees at the Central Bureau of Statistics of Deli Serdang Regency as many as 39 people using the slovin formula. The results of this study indicate that there is a positive and significant influence between learning organization and competence variables on employee performance at the Central Bureau of Statistics of Deli Serdang Regency. In the F test, it is known that the learning organization and competence variables together affect the employee performance variable at the Central Bureau of Statistics of Deli Serdang Regency positively and significantly. In the t-test, it is known that learning organization has a more dominant effect on employee performance at the Central Statistics Agency, Deli Serdang Regency. The results obtained in this study indicate that partially positive and significant effect. R Square value = 0.733, meaning that 73.3% of the factors that influence performance can be explained by independent variables (Learning Organization and Competence) while the remaining 26.7% is explained by other factors not examined in this study.